Acute Renal Failure Secondary to Tuberculosis: A Diagnostic Challenge. (22nd March 2012) - Khilji, Saeed I.; Kok, Hong Kuan; Wong, Limy; Dorman, Anthony M.; Walshe, J. Joseph
Abstract : Tuberculosis is a multiorgan disease with varied clinical presentations and is reemerging due to increasing immigration and globalization. We present the case of an immigrant female patient who developed acute renal failure with clinical and biochemical features suggestive of lupus nephritis but with a timely renal biopsy showing caseating granulomata in the renal parenchyma consistent with renal tuberculosis. Despite treatment with antituberculosis treatment and resolution of TB on repeat renal biopsy, she remained haemodialysis dependent. We discuss the diagnostic challenges faced in this presentation and also explore possible differential diagnoses. This rare presentation highlights the importance of renal biopsy in the diagnosis and treatment of acute renal failure and the atypical presentation of tuberculosis.